Mice lacking two testis-specific cytoplasmic poly(A)-binding proteins, PABPC2 and PABPC6, exhibit normal spermatogenesis and fertility - Yuka ISONO; Yuko KAKU; Yoshinori KANEMORI; Shin-ichi KASHIWABARA (The Journal of Reproduction and Development)
The cytoplasmic poly(A)-binding protein (PABPC) plays a central role in the life of poly(A) mRNAs, including their stability, translation, and decay. In addition to the nearly ubiquitous PABPC1, two testis-specific PABPCs, PABPC2 and PABPC6, are present in rodents, while one specific PABPC, PABPC3, is found in primate testes. These three PABPC proteins are each encoded by intronless genes that may have diverged independently due to the retroposition of prototypical Pabpc1 or PABPC1. PABPC2 and PABPC6 are distinguished from PABPC1 in that they barely associate with translationally active polysomal mRNAs and are enriched in male germ cell-specific nuage, termed chromatoid bodies. Despite these unique characteristics, spermatogenesis and male fertility were not compromised in mutant mice lacking either PABPC2 or PABPC6, suggesting functional redundancy between the two proteins. Here, we produced double-mutant mice lacking both PABPC2 and PABPC6 and found that the simultaneous absence of these two proteins failed to affect testicular protein synthesis, spermatogenesis, or male fertility in vivo. These results suggest that the functions of PABPC2 and PABPC6 are redundant with those of other co-existing PABPC proteins, including PABPC1. We propose that testis-specific PABPC proteins emerged because of transcriptional promiscuity in the testis.